Association of Methylenetetrahydrofolate Reductase C677T Gene Polymorphisms with Mild Cognitive Impairment Susceptibility: A Systematic Review and Meta-Analysis - Jiahui Sun; Xuefan Jiang; Ming Zhao; Lina Ma; Hui Pei; Nanyang Liu; Hao Li (Behavioural Neurology)
Background. Methylenetetrahydrofolate reductase (MTHFR) C677T (rs1801133) gene polymorphisms are related to a growing risk of Alzheimer’s disease; however, whether this association applies to mild cognitive impairment (MCI) remains unclear. Objective. We conducted this meta-analysis to evaluate the contribution of MTHFR C677T (rs1801133) gene variants to the risk of MCI. Methods. PubMed, Embase, Web of Science, and China National Knowledge Infrastructure databases were searched from their inception to March 21, 2021, with language restricted to English or Chinese. We used fixed or random effects to examine the association between MTHFR C677T (rs1801133) gene variants and MCI susceptibility. Forest plots of pooled odds ratios (ORs) and 95% confidence intervals (CIs) were generated. Results. Eight articles with 2,175 participants were included in the present meta-analysis. There was no significant association between MTHFR C677T (rs1801133) gene variants and MCI susceptibility under the allelic (OR, 1.318; 95% CI, 0.964–1.801; p=0.084), dominant (OR, 1.296; 95% CI, 0.925–1.817; p=0.132), recessive (OR, 1.397; 95% CI, 0.845–2.312; p=0.193), heterozygous (OR, 1.031; 95% CI, 0.855–1.243; p=0.749), or homozygous (OR, 1.506; 95% CI, 0.850–2.667; p=0.160) models. Conclusion. The results suggest that MTHFR C677T (rs1801133) gene polymorphisms are not associated with MCI susceptibility. However, large-scale studies covering various factors are required.